Solve for y -12-3y=12

Math
-12-3y=12
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 12 to both sides of the equation.
-3y=12+12
Add 12 and 12.
-3y=24
-3y=24
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3y=24 by -3.
-3y-3=24-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3y-3=24-3
Divide y by 1.
y=24-3
y=24-3
Divide 24 by -3.
y=-8
y=-8
Solve for y -12-3y=12

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top